The Importance of a Virtual Educational Museum in Culture and Sustainable Development. Students’ attitudes in High School. - Καμπουροπούλου, Μαρία; Φώκιαλη, Πέρσα; Στέφος, Στάθης (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The study examines the attitudes of students towards the course of the local Art and the Culture and the creation of a virtual Educational Museum. Central axis was a team project of the High school in Ialyssos, Rhodes which combined the course of local history and culture by collecting local Art items from private collections, digitizing them and creating a virtual training Folklore Museum on the school website. After the completion of the project, 100 students participated in the survey and answered a questionnaire concerning the teaching intervention. The analysis showed that most of the students learned how to create a virtual Museum and more about Folk Art, Culture Heritage and its meaning and realized how important this is for the sustainable development of their place. The goal of this study is to present the results of the multidimensional Analysis of the questionnaire which shows the differentiation criteria of the students. The results showed that the majority of the students are positive towards using the virtual Educational Museum and believe that their dealing with Folk Art and Culture should be implemented in High schools’ education.